Christologie der Beziehung - Begegnungen mit Frauen im Markusevangelium - Breuer, Saskia Rebecca; Taschl-Erber, Andrea (Personal Christology)

Diskriminierungssituationen im Praxissemester aus Sicht von Lehramtsstudierenden - Truong, Ha My; Vogelsang, Christoph
Diskriminierungserfahrungen können sich negativ auf die Kompetenzentwicklung von Schülerinnen und Schülern auswirken, was wiederum Bildungsungerechtigkeit zur Folge haben kann (Hummrich, 2023). Um solchen Dynamiken frühzeitig entgegenzuwirken soll in der Lehrkräfteausbildung, nach den Standards der Kultusministerkonferenz (KMK) auch der reflektierte Umgang mit Diskriminierung gefördert werden: „Die Absolventinnen und Absolventen […] analysieren Konflikte und kennen Methoden der konstruktiven Konfliktbearbeitung sowie des Umgangs mit Gewalt und Diskriminierung“ (KMK, 2019, S.10). Ein wichtiger Bestandteil der universitären Phase ist das Praxissemester (PS), das in NRW ein fünfmonatiges Schulpraktikum umfasst. Obwohl sich bereits einige Studien mit Diskriminierungserfahrungen an Schulen (z.B. Höhl, 2021; Ziemes, 2024) und in der Lehrkräfteausbildung (Fereidooni, 2015) auseinandersetzten, gibt es bislang keine quantitative Studie, die die Perspektive von Lehramtsstudierenden im PS systematisch einbezieht. An der Universität Paderborn wurde daher in einer explorativen Querschnittsbefragung (N=431) erfasst, inwiefern Lehramtsstudierende Diskriminierungssituationen im Praxissemester beobachten und wie sie ihre Kompetenzen im Umgang mit Diskriminierung in der Schule einschätzen. In den Ergebnissen zeigt sich, dass die Studierenden das Differenzmerkmal Migrationshintergrund mit 31% in den beobachteten Fällen als Diskriminierungsgrund nannten. Zudem nahmen sie wahr, dass am häufigsten die Schüler*innen untereinander abwertend über andere Mitschüler*innen sprachen. Dies kam bei 67% der Befragten mindestens einmal im PS vor. Bei den Studierenden selbst haben 11% mindestens einmal im PS Diskriminierung durch Lehrkräfte erfahren und mit 14% wurden sie mindestens einmal von Schüler*innen diskriminiert. Die Studierenden hielten sich aber überwiegend für ausreichend kompetent im Umgang mit Diskriminierungssituationen.

Diskrimierungserfahrungen im Praxissemester - Truong, Ha My

The quality of digital curriculum resources for mathematics in German educational policy - Rezat, Sebastian (ZDM – Mathematics Education)
This paper examines the governance and quality control of digital curriculum resources (DCR) for K-12 mathematics education in Germany. It focuses on approval processes and criteria set by the 16 federal states, arguing that these have the potential to influence the development of DCR. Using qualitative content analysis, the study explores three research questions: which DCR require official approval, the criteria applied for approval, and the extent to which these criteria are mathematics-specific. Findings indicate that 10 federal states maintain official approval systems, covering digital equivalents of printed textbooks and selected supplemental materials. However, most DCR fall outside these regulated processes, leaving their evaluation largely to individual schools and teachers. The study identifies 17 categories of quality criteria, but reveals a lack of detailed, mathematics-specific requirements. Instead, many criteria are broad references to didactical principles and educational goals, leaving the interpretation and application of these quality standards open-ended. Subject-specific criteria are included but remain limited in specificity. The study underscores the need for research-informed, mathematics-specific quality standards to guide DCR development and approval, emphasizing their importance amidst challenges like artificial intelligence. Policymakers are urged to adopt clearer criteria to ensure high-quality DCR to be used in schools.
Keywords: governance; digital curriculum resources; digital textbooks; digital curriculum materials; quality

Generation time for biexact functors and Koszul objects in triangulated categories - Letz, Janina Carmen; Stephan, Marc (Doc. Math.)

Koszul homomorphisms and universal resolutions in local algebra - Briggs, Benjamin; Cameron, James C.; Letz, Janina Carmen; Pollitz, Josh (Forum Math. Sigma)

An equivalence linking CM-types $A_∞$ and $D_∞$ - Cummings, Charley; Gratz, Sira; Kirkman, Ellen; Letz, Janina Carmen; Rock, J. Daisie; Špenko, Špela

Regular sequences for triangulated categories - Kekkou, Antonia; Letz, Janina Carmen; Stephan, Marc

Realization functors in algebraic triangulated categories - Letz, Janina Carmen; Sauter, Julia (Abh. Math. Semin. Univ. Hambg.)

Tensor extriangulated categories - Bennett-Tennenhaus, Raphael; Goodbody, Isambard; Letz, Janina Carmen; Shah, Amit (J. Algebra)

Transfer of A-infinity structures to projective resolutions - Letz, Janina Carmen (Comm. Algebra)

The Rouquier dimension of the category of perfect complexes over a regular ring - Letz, Janina Carmen

Open Educational Resources (OER) - Weber, Tassja (Praxishandbuch Hochschullehre II)
Was macht gelungene Hochschullehre aus? Und an welchen Stellschrauben kann ich drehen, um die eigene Lehre zu verbessern? Das zweibändige "Praxishandbuch Hochschullehre" bietet als Standardwerk Orientierung bei didaktischen Fragen und beleuchtet aktuelle Entwicklungen des Bereichs. In Band II setzen sich die Beiträger:innen mit dem Prüfen und Bewerten von Studierenden auseinander, geben Tipps zu Feedback und Evaluation und widmen sich den Themen Digitalisierung, Nachhaltigkeit sowie Barrierefreiheit. Angereichert mit Abbildungen, Definitionen, Schlagworten, Schritt-für-Schritt-Anleitungen und einem umfangreichen Glossar lädt der anwendungsorientierte Leitfaden alle Lehrenden dazu ein, sich aktiv mit den wesentlichen Inhalten der Hochschullehre auseinanderzusetzen – unabhängig von Fachrichtung und Erfahrungsstufe. utb+: Zusätzlich zum Buch stehen zu einigen Beiträgen hilfreiche Materialien wie Verlaufsprotokolle, Vorbereitungs- und Bewertungsbögen zum Download bereit. Verfügbar in drei Ausgabearten: Print, E-Book (PDF), Web-Book (Buch als Website). Das Web-Book integriert Buchinhalte und digitale Elemente. Für Print und E-Book sind die digitalen Materialien über utb.de kostenlos abrufbar.

Commutator-free Cayley methods - Wembe Moafo, Boris Edgar; Offen, Cristian; Maslovskaya, Sofya; Ober-Blöbaum, Sina; Singh, Pranav (J. Comput. Appl. Math)
Differential equations posed on quadratic matrix Lie groups arise in the context of classical mechanics and quantum dynamical systems. Lie group numerical integrators preserve the constants of motions defining the Lie group. Thus, they respect important physical laws of the dynamical system, such as unitarity and energy conservation in the context of quantum dynamical systems, for instance. In this article we develop a high-order commutator free Lie group integrator for non-autonomous differential equations evolving on quadratic Lie groups. Instead of matrix exponentials, which are expensive to evaluate and need to be approximated by appropriate rational functions in order to preserve the Lie group structure, the proposed method is obtained as a composition of Cayley transforms which naturally respect the structure of quadratic Lie groups while being computationally efficient to evaluate. Unlike Cayley-Magnus methods the method is also free from nested matrix commutators.

Three-Phase Instantaneous Current Controller for Unbalanced Grid Inductors Without DQ Transform for Cascaded H-Bridge Converters - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2025 Energy Conversion Congress & Expo Europe (ECCE Europe))
Three-phase cascaded H-bridge converters (CHBs) in star configuration require reliable current controllers to evenly charge the module DC-link capacitors. Conventionally, a current control in dq-coordinates is utilized. At steady state, the resulting calculated reference arm voltages are sinusoidal, have identical amplitudes and show a phase shift of 120 degree to each other. For balanced grid inductors, the resulting grid currents also have the same amplitude. However, own simulations show that unbalanced grid inductors always lead to different grid current amplitudes (4% difference in this case). As a result, the averaged charging module powers differ and the peak DC-link capacitor voltage rises as well. In the first step, an adaptation of an existing zero-sequence voltage injection is proposed. For balanced grid inductors, it converges to the 3rd harmonic voltage injection which can reduce the peak-to-peak DC-link voltage ripple up by to 50% and balances the power between the phases. However, unbalanced grid inductors still lead to the same unbalanced grid currents of 4%. Therefore, a new method with 4 integrators based on linear regression is proposed to achieve sinusoidal grid currents for unbalanced inductors. The proposed method has a similar transient dynamic as the conventional dq control, but balances the grid currents nearly ideally. Simulation results of a 1MW cascaded H bridge and a scaled-down prototype verify the proposed method.
Keywords: Cascaded H-Bridge; Current Control; dq Transformation; Linear Regression; Unbalanced Inductors

Microscopic approach to the quantized light-matter interaction in semiconductor nanostructures: Complex coupled dynamics of excitons, biexcitons, and photons - Rose, Hendrik; Schumacher, Stefan; Meier, Torsten (Physical Review B)

Unterrichtsintegrierte Diagnostik im Förderschwerpunkt Sprache – ein Überblick - Jonas, Kristina; Abel, Miriam Katharina (Sprachförderung und Sprachtherapie in Schule und Praxis)

Modelling, Argumentation and Problem-Solving in the Context of Outdoor Mathematics - Jablonski, Simone

The Impact of a MOOC: Long-Term Analysis of Teachers' Learning Outcomes and Practices - Taranto, E; Jablonski, S; Recio, T; Cunha, E; Ludwig, M; Mammana, MF

"Sohn, dein Blut muß ich vergießen" - Ritual und Opfer in den Abraham-Oratorien des 19. Jahrhunderts - Höink, Dominik; de Vos, J. Cornelis (Musik im Ritual - Rituale in der Musik)